Aspirations and Challenges of Mothers of Marginalized Early Years Children: Reflections from Bhopal City, India - Srivastava, Ritika (Voices of Teachers and Teacher Educators, 2023)
Global policies and research accept the significance of early years learning and care for children. This paper explores mothers’ aspirations and challenges in caring for and educating marginalised early years children in the Indian city of Bhopal. The article examines children’s care, safety, and living conditions by presenting the views of mothers whose children attend fee-free non-government and government organization-run ECCE centers. The idea of school readiness has also been elicited from the perspective of participant mothers. The data reveals the structural inequality embedded in accessing quality primary care and early literacy opportunities for marginalised children in India.